Impacto do ICMS E IRPF na distribuição de renda no Estado do Ceará - Alves, Lúcio Flávio (2010)
This paper presents an analisys of the impact of Imposto Sobre Operações relativas à Circulação de Mercadorias e sobre Prestações de Serviço de Transporte Interestadual e Intermunicipal e de Comunicação - ICMS and of Imposto de Renda Pessoa Física-IRPF in the distribution of income in the state of Ceará. The object of the study is to identify if the ICMS is regressive, penalizing people of low economic classes, and if the IRPF is worth the regressive effect of ICMS. In the paper information about consumption of 50 products of the families of Ceará contained in POF-IBGE 2002/2003 was used. The method used to construct the regression function of the sample was the ordinary least squares. Engel curves were estimated in order to determine the income elasticities of demand for selected products from the corresponding expenditures. The results show that the IRPF offsets the regressivity of ICMS, and are the poorer classes who bear in relative terms with the payment of ICMS in the state of Ceará.